Detection of pulmonary tuberculosis through mobile X-ray based active case-finding in Pakistan: a retrospective analysis from programmatic screening of 1 214 289 individuals from 2017 to 2021 - Andrew Copas; Hanif Esmail; Jacob Creswell; Saira Khowaja; Aamir Khan; Syed Mohammad Asad Zaidi (BMJ Global Health, 2025)
Recent evidence suggests that community-wide active case finding (ACF) can reduce tuberculosis (TB) incidence and prevalence. Mass-screening at the community level, supported by mobile digital chest X-ray units, is now being scaled up by programmes across high burden countries. However, there is limited evidence of case-detection yields from programmes conducting ACF at scale in low-resource settings. We retrospectively analysed aggregate data from mobile X-ray screening events (called ‘camps’) in Pakistan from Q3 2017 to Q2 2021. A total of 11 327 camps were conducted that screened 1 214 289 individuals and detected 7625 cases of All-Forms TB (AF–TB), among whom 3500 (45.9%) were bacteriologically confirmed (B+) and the remaining were treated empirically. The yield for B+ and AF-TB per 100 000 population screened nationally was 289 (95% CI: 279 to 298) and 631 (95% CI: 617 to 646), respectively. Yield of TB detected from screening was highly variable between regions of Pakistan, ranging from 70 to 678 per 100 000 B+ and 76 to 1136 per 100 000 for AF–TB. Our findings have two major lessons for TB programmes. First, there was significant geographical variation in yields of both B+ and AF-TB, supporting targeting of interventions in areas of high prevalence to maximise the intervention’s effectiveness. Second, more than half of TB cases were treated empirically, and approaches to improve sample collection, linkage to diagnostics, non-sputum based tests and standardisation of treatment for bacteriologically unconfirmed TB need to be concurrently prioritised by programmes considering scale-up of mobile X-ray-based ACF.